Prenatal and postnatal management of congenital bronchial atresia (CBA): single tertiary center report. (18th August 2017) - Yu, Gang; Xia, Bo; Wang, Zhu; Huang, Baisha; Zhang, Ying; Hong, Chun; Shang, Ning; Tang, Jing
Abstract: Objective : To summarize our diagnosis and management experience of congenital bronchial atresia (CBA). Methods : A retrospective review was conducted, clinical data were collected of all patients with CBA. Results : Among the nine patients (5 males and 4 females), six cases with right side and three cases with left cases, including one patient with mainstem bronchial atresia (MBA), two cases with lobar bronchial atresia (LBA), six cases with segmental bronchial atresia (SBA). Eight were diagnosed as congenital cystic adenomatoid malformation (CCAM) type III by ultrasound (US) in prenatal. The MBA patient was diagnosed by computed tomography (CT) and bronchofibroscopy, only two patients by pathological findings and the other six patients by CT. Five cases were accompanied by CCAM, one case with bronchopulmonary sequestration (BPS), two cases with emphysema. Eight cases except MBA were underwent thoracoscopic surgery treatment and had favorable prognosis. Two cases with LBA merged with complication of pectus excavatum after surgery. One case with MBA had no surgery and died in the 13 days old. Conclusions : CBA is an easily misdiagnosed disease from pathologic conditions, definitive diagnosis of this condition depends on combination CT or clinical pathologic diagnosis. Thoracoscopic resection is a safe and feasible treatment of CBA in experienced hands.